Application of Pattern of Islamic State Revenue Policy to Improve the Ability of Indonesia’s Fiscal - Any Setyaningrum (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The aim of this study is to analyze the possibility of Islamic state revenue to improve the ability of Indonesia’s fiscal. This thing is important in the way to diversify the fiscal instruments in Indonesia. The result shows that several Islamic revenues instruments still relevant to applied in Indonesia, exclude the ghanimah and Jizya. But, it is necessary to adjust the nomenclature and connectivity with state financial regulations. The application does not have to be exclusive and labels associated with Islam, but should be more focused on the exploration of universal values and utility, which is inherent in all of Islam income instruments.DOI: 10.15408/aiq.v7i2.1702